Enterprises, Workers, and Skills in Urban Timor-Leste - Das, Maitreyi Bordia; O'Keefe, Philip (World Bank, Washington, DC, 2012)
Like many low-income countries, Timor-Leste faces challenges in providing employment for and increasing the skills of its labor force-challenges made more acute by high fertility rates, a very young population, and the capacity constraints of a new nation. However, there is limited information for policymakers to formulate appropriate policies. The paper presents findings of the first urban enterprise survey in independent Timor-Leste. It explores several aspects of the Timorese urban labor market, including the profile of formal and informal enterprises, their behavior in terms of employment and wage-setting practices, and constraints on firm growth. It also presents findings on the skills and training needs of urban employers, and constraints faced in overcoming skills shortages. It finds a highly informal urban enterprise scene, where even "formal" enterprises are largely micro-enterprises. While there has been considerable action in terms of new firm creation since independence, there is already surprisingly low job creation or destruction. This is driven by a number of constraints inside and outside the labor market. With respect to wages, the impacts of the informal minimum wage policy inherited from the interim international administration suggest the need for caution in future wage policy development. While employers identify many skills gaps, basic literacy, numeracy, and language skill needs dominate, and employers appear to value short courses and less formal modes of skills training to address their needs. The paper concludes with suggestions for addressing the key constraints identified.